Analisis Kemampuan Berpikir Kritis Siswa Kelas VII SMPN 20 Kota Bengkulu dalam Menyelesaikan Soal Cerita Materi Aljabar Ditinjau dari Gender - Viandrayanti, Asri; Syafri, Fatrima Santri (Papanda, 2026)
This study aims to describe the critical thinking skills of seventh-grade students in solving word problems on algebra material from a gender perspective. This study uses a descriptive qualitative approach. The research subjects consisted of 29 seventh-grade students of SMP Negeri 20 Bengkulu City, with five students selected as the main subjects based on their level of critical thinking skills and gender representation. Data collection techniques included written tests, observations, interviews, and documentation. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing.Findings reveal that, in aggregate, the learners’ mathematical critical-reasoning acuity resides at a middling tier, with 38% situated within the exceptionally high category, 48% classified as high, 7% occupying the moderate bracket, and 7% falling into the rudimentary level. Learners within the exceptionally high tier demonstrated the ability to articulate explanations with exactitude, adopt appropriate problem-solving stratagems, and procure accurate solutions. Conversely, those in the high category exhibited comprehension of algebraic notions yet were occasionally inattentive in executing procedural sequences. Students within the moderate classification manifested misjudgements in selecting suitable solution pathways, whereas those in the rudimentary group encountered impediments in deciphering essential information and constructing mathematical representations, often resorting to conjectural responses. The gender-oriented appraisal indicated the presence of stylistic and strategic discrepancies between male and female students in confronting problem-solving tasks, although such distinctions did not exert a substantive influence on their overall critical-reasoning competence. Broadly considered, this study accentuates the necessity of fortifying algebraic conceptualisation and sustaining systematic problem-solving practice as a means of enhancing learners’ critical-thinking aptitude.